Students’ performance at the Baccalaureate Exam during the COVID-19 pandemic – Evidence from Romania - Andreea MIRICĂ; Octavian CEBAN; Ionela-Roxana PETCU (Communications of International Proceedings, 2022)
Countries face a major challenge in terms of learning inequalities and Romania makes no exception. Performing well at Baccalaureate exam is a very important topic for all students as this places at risk the number occupied university places and adds extra burden on the parent shoulders on top of existing COVID-19 pandemic concerns. Our research aims to evaluate the impact of demographic as well as educational characteristics on Baccalaureate performance and their influence in failing this exam. The dataset in the present research uses microdata extracted from the Ministry of Education database. ANOVA and logistical regression results highlight that these characteristics influence the probability to fail the exam in terms that males still have a higher probability to fail compared to females and rural candidates in Romania have less chances to pass compared to their counterparts. The highest performance was obtained by students with a theoretical background while the probability to fail is the highest for the ones with technological background or attending evening classes.
Keywords: Romania; baccalaureate exam; logistic regression; learning inequality; academic achievements